Long-Term Effect of Therapeutic Horseback Riding in Youth With Autism Spectrum Disorder: A Randomized Trial - Gabriels, Robin L.; Pan, Zhaoxing; Guérin, Noémie A.; Dechant, Briar; Mesibov, Gary (Frontiers in Veterinary Science, 2018)
http://clinicaltrials.gov; NCT02301195. Abstract This paper presents six-month follow-up data of 44% (N= 64/116) of participants (ages 6-16 years) with a diagnosis of autism spectrum disorder, who participated in a previously-published randomized controlled trial of therapeutic horseback riding (THR) compared to a no-horse contact active control. The objective of this study was to examine whether significant improvements of irritability, hyperactivity, social and communication behaviors observed in participants randomized to receive a 10-week manual-based THR intervention were sustained six months after the intervention conclusion. Participants' caregivers from both the THR (n = 36) and active control (n = 28) groups completed a measure of irritability and hyperactivity behaviors (primary outcome variables). Additionally, only the THR group participants completed the full battery of study outcomes assessments. Between group comparisons examining the extended interval from baseline (one-month pre-intervention assessment) to six-months after the intervention revealed that the THR group maintained reductions in irritability behavior at a 0.1 level (effect size=0.32, p=0.07). (Effect size=0.32, p=0.07), which was 73% of efficacy preserved from the primary post-intervention endpoint (within one month post-intervention). Hyperactivity behaviors did not sustain this same trend. Comparisons from baseline and six-months after the intervention revealed that the THR group sustained significant initial improvements made in social and communication behaviors, along with number of words and different words spoken during a standard language sample. This is the first known study to examine and demonstrate the longer-term effects of THR for individuals with ASD and warrants a more thorough evaluation of whether the effects of THR are maintained for at least six-months after the intervention compared to a control.